Feasibility of Active Surveillance for Acute Respiratory Illnesses among Staff in Pediatric Long-term Care Facilities. (4th October 2017) - Wilmont, Sibyl; Neu, Natalie; Alba, Luis; Prill, Mila M; Kim, Lindsay; Gerber, Susan I; Garg, Shikha; Larson, Elaine; Saiman, Lisa
Abstract: Background: Acute respiratory infections (ARIs) are common in pediatric long-term care facility (pLTCF) residents, but little is known about the burden of ARIs in staff in these settings. We assessed the feasibility of active surveillance for ARIs among pLTCF staff who performed direct resident care. Methods: We enrolled 50 staff members from 2 pLTCFs in New York to participate in ARI surveillance from December 7, 2016 to May 7, 2017. An ARI case was defined as having >2 symptoms including: self-reported fever/feeling feverish, runny nose/nasal congestion, chills, shortness of breath, wheezing, new/different cough, new/different sputum, sore throat/scratchy throat, headache, or myalgias. The study team sent weekly text or email messages (per participant preference) listing ARI symptoms. Staff responded if they were sick or not. Participants responding "Yes" were contacted by text or email to confirm ARI symptoms. Staff with a confirmed ARI had mid-turbinate and throat swabs obtained <4 days of ARI onset and weekly for 4 weeks of follow-up to assess duration of viral shedding. Swabs were obtained by the study team or participants themselves. Results: During the first 14 weeks of surveillance, 700 messages were sent. A higher percentage of participants responded to text (95%, 522/550) compared with email (85%, 128/150) messages (chi-square test, P < 0.05). Of the 26 self-reported ARIs, 20 (77%) ARIs in 18 participants, fulfilled the case definition. Onset swabs were obtained for 14 (70%) of 20 ARIs including 14 mid-turbinate and 5 throat swabs. For follow-up swabs, 74 (46%) of 160 were obtained (51 mid-turbinate and 23 throat). All 4 follow-up swabs were obtained for 7 (35%) of 20 episodes. The study team collected 64 (69%) of 93 swabs, and preliminary results of viral testing are pending. Conclusion: During the 14 week surveillance period, ARIs occurred in over one-third of participants. Participants were more likely to respond to text than email messages. Suboptimal collection of onset and follow-up swabs reflected staff absences and workload. Fewer throat swabs than mid-turbinate swabs were collected reflecting participant discomfort obtaining throat swabs. Different strategies are needed to improve collection of respiratory specimens in this population. Disclosures: S. Wilmont, Columbia University Medical Center Pediatric Infectious Diseases: Employee, Salary.